Encheiridion de Epicteto - Aldo Dinucci (Autores Gregos e Latinos - Textos, 2014)
In this comedy of deception and conflict of values, the young Philolaches, taking advantage of the absence of the father, became indebted due to the parties he has hosted and the purchase of his beloved courtesan. The unexpected return of the senex requires the ingenious scheme of the slave Tranio. Once given the news that the house was haunted, the money loaned from the usurer was justified, to purchase the house of the neighbor. After all the scenes of quid pro quo were clarified, Callidamates, a friend of Philolaches, conveys the comedy to a happy ending - after stabilizing the situation, arguing that the money will be restored, the senex Theopropides gives his forgiveness.